Depression and Anxiety Among Quarantined People, Community Workers, Medical Staff, and General Population in the Early Stage of COVID-19 Epidemic - Li, Xiaoling; Yu, Hegao; Yang, Weiqiang; Mo, Qihua; Yang, Zhanggui; Wen, Shuangshuang; Zhao, Fei; Zhao, Weishun; Tang, Yongyan; Ma, Liang; Zeng, Ruifen; Zou, Xia; et al. (Frontiers in Psychology, 2021)
Background We described the prevalence of anxiety and depression related to COVID-19 pandemic among different types of population and examined their potential risk factors. Methods Across-sectional survey was conducted to collect demographic characteristics, exposure histories, and many other concerns about COVID-19. The Zung’s self-rating anxiety scale (SAS) and self-rating depression scale (SDS), followed by a four-step multiple logistic regression analysis was performed to identify factors associated with mental health outcomes. Results Out of 3,303 participants, the quarantined people (40.9%), community workstation staffs-policemen-volunteers (CPV) (36.4%) and general public (30.7%) reported higher percentages of depression than the general medical staff (18.4%). Moreover, the quarantined people (19.1%) also showed higher prevalence of anxiety than the general public (9.1%) and the general medical staff (7.8%). The quarantined people had the highest risk of anxiety and depression, whereas the self-rated health was negatively associated with the risks of anxiety and depression. Younger age group (18 to 30 years) showed higher risks of anxiety (OR=6.22, 95%CI=2.89-13.38, p<0.001) and depression (OR=3.69, 95%CI=2.40-5.69, p<0.001). People who had exposure history or contact from Hubei province after December 1, 2019(OR=1.57, 95%CI=1.07-2.30, p<0.001), had family or friends engaged in front-line health care work (OR=1.47, 95%CI=1.02-2.14, p<0.001), had confirmed case nearby (OR=2.44, 95%CI=1.43-4.18, p<0.001) were all more likely to suffer from anxiety. Moreover, the negligence (OR=1.85, 95%CI=1.37-2.51, p<0.001) or overindulgence (OR=1.45, 95%CI=1.03-2.04, p<0.001) towards the epidemic information was associated with a higher risk of depression and anxiety. Conclusions Our findings show that the CPV and quarantined people were most at-risk population. We have identified that the young people, people with exposure histories and negligence or overindulgence towards epidemic information are in grave need of attention.